Analisis Disiplin Belajar Ditinjau dari Dukungan Sosial Teman Sabaya Siswa di SMA - Adilatunnisa, Adilatunnisa; Afdal, Afdal (YASIN, 2024)
Learning discipline is a condition where individuals show obedience in order to create an orderly life structure. Student learning discipline can be influenced by many factors, one of which is social support from peers. This research aims to analyze differences in students' levels of learning discipline in terms of peer social support. The research method used was descriptive quantitative with hypothesis testing carried out using Kruskal Wallis. The sample for this research was 104 students from SMA N 1 Lintau Buo, using a purposive sampling technique with special requirements. The results of this research indicate that the level of student learning discipline in terms of peer social support is in the medium category. The results of the Kruskal Wallis test show a significance value of <0.001, that there is a significant difference in the average learning discipline based on peer social support. Based on the results of this research, it shows that there are real differences in students' levels of discipline when viewed from high, medium and low peer social support.